Calculation of Lipschitz constants enabling advanced root finding in electrical network simulation - Kuring, Carsten; Dobusch, Julian; Dürbaum, Thomas (19th IEEE Workshop on Control and Modeling for Power Electronics (COMPEL 2018), 2018)
Power electronic circuits are highly complex systems with a large amount of system parameters. Thus, the design optimization process requires an accurate simulation technique featuring high computational efficiency. Achieving an efficient converter design involves large parameter studies. Discrete modelling represents a promising tool for fast and accurate simulation. However, reliable zero crossing detection is absolutely necessary. Root observation by means of Lipschitz constant addresses this issue but anticipates the knowledge of a Lipschitz constant. This paper proposes a method to determine Lipschitz constants in the context of electrical network simulation.
Keywords: Lipschitz constants; zero crossing detection; electrical network simulation; first zero crossing point; LLC